Physicians' communication styles as correlates of elderly cancer patients' satisfaction with their doctors. (27th October 2015) - Finkelstein, A.; Carmel, S.; Bachner, Y.G.
Abstract : Physician–patient communication style is of utmost importance to patients with life‐threatening diseases. This study identifies the most desired physician communication style by older cancer patients; and examines which of the studied communication styles significantly explains cancer patients' satisfaction with family physicians. A total of 200 older cancer patients, with average age of 75 years, participated in the study, yielding a response rate of 42%. Prospective respondents were randomly selected from the list of cancer patients in the central geographical district of Israel's second largest Health Maintenance Organization fund. Respondents rated their satisfaction with physicians as relatively high. All three communication styles studied were found to be associated with patient's satisfaction. Associations were found between self‐rated health, time since the diagnosis of cancer and satisfaction. Women were less satisfied than men with their physicians. Two variables emerged as significant predictors of satisfaction: the physician's caring communication style and patient's gender. Intervention programmes should focus on elevating physicians' awareness of the importance of their communication with cancer patients in general, and of the caring communication style in particular.